2020
DOI: 10.1021/acsabm.9b01141
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Delivery of CD147 Antagonistic Peptide-9 Protects against Acute Ischemic Brain Injury and tPA-Induced Intracerebral Hemorrhage in Mice

Abstract: CD147 has emerged as a potential therapeutic target in many human diseases. We have demonstrated that inhibition of CD147 using its function-blocking antibody ameliorates acute ischemic brain injury and promotes long-term functional recovery in mice. Recently, peptide–nanoparticle conjugates have emerged as powerful tools for biomedical applications. The present study aimed to investigate the therapeutic potential of CD147 antagonist peptide-9 (AP9) in acute ischemic stroke in mice using nanomaterial as the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“… The administration of APN via intravenous injection at a dose of 2.5 mg/kg led to an improvement in acute stroke outcome on the third day. [ 145 ] αCD147 mice, tMCAO once daily i.v. Injection for 3 days beginning 4 h after ischemia onset.…”
Section: Immunomodulatory Therapeutic Strategies To Treat Ischemic St...mentioning
confidence: 99%
“… The administration of APN via intravenous injection at a dose of 2.5 mg/kg led to an improvement in acute stroke outcome on the third day. [ 145 ] αCD147 mice, tMCAO once daily i.v. Injection for 3 days beginning 4 h after ischemia onset.…”
Section: Immunomodulatory Therapeutic Strategies To Treat Ischemic St...mentioning
confidence: 99%
“…AP9 can target EMMPRIN to prevent cancer invasion and metastasis ( 87 , 88 ). A recent study showed that AP9, likely through inhibition of EMMPRIN-mediated MMP-2/-9 activation and ECM degradation, attenuates ischemia/reperfusion injury in an experimental model of acute myocardial infarction ( 89 ), and inhibits MMP-9 and MMP-3 in the ischemic brain and plasma ( 90 ).…”
Section: Treatments That Target Emmprin In Brain Ischemia and Ichmentioning
confidence: 99%
“…It is known that MMP-9 is able to induce BBB leakage by interfering with brain endothelial cell tight junctions [101]. Thus, MMP-9 silencing and/or its direct inhibition could result in an interesting treatment for hyperacute stroke [69][70][71]. In this regard, NPs conjugated or loaded with an MMP-9 inhibiting peptide [69], tissue inhibitor of matrix metalloproteinases 1 (TIMP-1) [70], or CD147 antagonist peptide-9 [71] were able to cross the BBB and inhibit MMP-9 [69].…”
Section: Nps In the Hyperacute Phase Of Strokementioning
confidence: 99%